Technological Innovations for Improving Cassava Production in Sub-Saharan Africa - Mbanjo, Edwige Gaby Nkouaya; Rabbi, Ismail Yusuf; Ferguson, Morag Elizabeth; Kayondo, Siraj Ismail; Eng, Ng Hwa; Tripathi, Leena; Kulakow, Peter; Egesi, Chiedozie (Frontiers in Genetics, 2021)
Cassava is crucial for food security of millions of people in sub-Saharan Africa. The crop has great potential to contribute to African development and is increasing its income-earning potential for small-scale farmers and related value chains on the continent. Therefore, it is critical to increase cassava production as well as its quality attributes. Technological innovations could be primary drivers of this change. This paper highlights genomic tools and resources available in cassava. We provide a glimpse of how these resources have been used to screen and understand the pattern of cassava genetic diversity on the continent. We review the approaches currently used for phenotyping cassava traits. The approaches used to link genotypic and phenotypic information, dissect the genetics architecture of key cassava traits, and identify quantitative trait loci/markers significantly associated with those traits are highlighted. We examine how knowledge acquired has been utilised and how it could contribute to crop improvement. We explore major approaches applied in the field of molecular breeding for cassava, their promises and limitations. The role of national agricultural research systems as key partners for sustainable cassava production is examined.